Medical care of newborns born to mothers with confirmed or suspected severe acute respiratory syndrome coronavirus 2 infections in Japan. Issue 1 (11th November 2021) - Morioka, Ichiro; Toishi, Satoshi; Kusaka, Takashi; Wada, Kazuko; Mizuno, Katsumi
Abstract: Background: There are currently no definitive guidelines regarding newborns born to mothers with confirmed severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection. This study aimed to investigate the medical care and management that provided or would provide for such newborns. Methods: A web survey was conducted between September and October 2020. A total of 624 hospitals, which generally accept pregnant women for delivery, were involved in this study. The survey included the number of newborns born to mothers with confirmed SARS‐CoV‐2 infection and evaluated policies regarding the medical care and management of newborns born to mothers with confirmed or suspected SARS‐CoV‐2 infection. Results: Pregnant women with confirmed or suspected SARS‐CoV‐2 infection were accepted or planned to be accepted in 54% (334) of the hospitals. Out of 52 newborns born to mothers with confirmed SARS‐CoV‐2 infection, SARS‐CoV‐2 RNA was detected from the nasopharyngeal swab of one newborn shortly after birth. The types of personal protective equipment during the delivery, the separation of the newborns from the mothers, the SARS‐CoV‐2 testing methods, and the use of incubators during the quarantine period were uniformly provided. However, the methods of ventilator treatment in the event of respiratory disorders, feeding during maternal isolation, and de‐quarantine and discharge criteria varied. Conclusions: This survey demonstrated that one newborn detected a SARS‐CoV‐2 RNA shortly after birth out of 52 newborns who were born to mothers with confirmed SARS‐CoV‐2 infection. The policies regarding medical care and management for these newborns in Japan were provided.